Divine subjection: the rhetoric of sacramental devotion in early modern England - Kuchar, Gary (Medieval & Renaissance literary studies, 2005)
"Combines theoretically engaged analyses with historically contextualized close readings to open new ways of understanding the relations between devotional literature and early modern English culture"--Provided by publisher